2019
DOI: 10.7150/jca.30081
|View full text |Cite
|
Sign up to set email alerts
|

Searching HPV genome for methylation sites involved in molecular progression to cervical precancer

Abstract: Background: Human Papilloma Virus has been considered as the main cause for cervical cancer. In this study we investigated epigenetic changes and especially methylation of specific sites of HPV genome. The main goal was to correlate methylation status with histological grade as well as to determine its accuracy in predicting the disease severity by establishing optimum methylation cutoffs.Methods: In total, sections from 145 cases genotyped as HPV16 were obtained from formalin- fixed, paraffin-embedded tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…However, we cannot exclude the possibility that this theory might be applicable for HPV16 in the future. Additional factors should be taken into consideration in order to lead to more accurate conclusions about cervical cancer risk, such as multiple HR-HPV infections, viral DNA integration, the methylation status of HPV DNA and mutations into the host target proteins ( Refs 13,18,34,[158][159][160].…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot exclude the possibility that this theory might be applicable for HPV16 in the future. Additional factors should be taken into consideration in order to lead to more accurate conclusions about cervical cancer risk, such as multiple HR-HPV infections, viral DNA integration, the methylation status of HPV DNA and mutations into the host target proteins ( Refs 13,18,34,[158][159][160].…”
Section: Discussionmentioning
confidence: 99%
“…An epigenetic change is defined as a change in the expression of host or viral genes without changes of the encoding DNA sequence [ 37 ]. DNA methylation is the most extensively studied epigenetic change in HPV-related cancers [ 50 ]. During DNA methylation, DNA methyltransferase enzymes covalently add methyl groups to cytosine preceding guanine (CpG) [ 51 ].…”
Section: Hpv-mediated Dna Methylationmentioning
confidence: 99%
“…Certain studies have demonstrated that methylation assays are a useful tool for triaging women with advanced HPV infections, although their performance is rather poor in on-going hrHPV infections that have not progressed yet to CIN3 or cervical cancer (97,(104)(105)(106). In addition, with advancements in technology, HPV DNA testing could be replaced by DNA methylation screening (95). At present, methylation testing is based on RT-qPCR to estimate the percentage of methylated DNA molecules in the sample for the targeted region (Fig.…”
Section: Dna Methylation For Cervical Screeningmentioning
confidence: 99%
“…In addition to host genes methylation, the methylation of viral genes exhibits high levels, particularly in capsid genes and late open reading frames. This has been associated with the progression of lesions from CIN2/3 to invasive cancer ( 95 , 96 ). In a study on HPV-infected Asian women with different grade of lesions, the methylation status of CpG islands in HPV16, 18, 52 and 58 was investigated.…”
Section: Epigenetic Alterations In Human Tumorsmentioning
confidence: 99%